Diseño de sistema de purificación para mejorar la calidad del aire interior de edificios en sectores con altos niveles de contaminación: caso de estudio barrió Carvajal (2021)
According to the evidence, they have affirmed that air pollution in Bogotá in recent years and according to the Encyclopedia of Health and Safety at Work, it is referenced that people located in urban areas spend most of their time performing sedentary activities in spaces indoors, during their working hours and in leisure time. As a consequence of this activity in closed spaces, there is an environmental problem which is affecting the indoor air quality of homes, causing a negative increase in public health indices, with patients suffering from respiratory diseases, since the exposure of the population for 24 hours to indoor air pollutants can cause fatal effects (total, cardiovascular), fatigue, shortness of breath, up to emergency hospital admissions for COPD chronic obstructive pulmonary disease and dependencies on oxygen bullets.